2017
DOI: 10.1007/s40279-017-0711-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validity of the Rating-of-Fatigue Scale

Abstract: ObjectiveThe purpose of these experiments was to develop a rating-of-fatigue (ROF) scale capable of tracking the intensity of perceived fatigue in a variety of contexts.MethodsFour experiments were carried out. The first provided the evidential basis for the construction of the ROF scale. The second tested the face validity of the ROF, and the third tested the convergent and divergent validity of the ROF scale during ramped cycling to exhaustion and 30 min of resting recovery. The final experiment tested the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
236
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(240 citation statements)
references
References 51 publications
1
236
1
2
Order By: Relevance
“…Participants were asked to rate their subjective perception of exertion (RPE), rating of general fatigue and perceived muscle pain using a 6–20 Borg RPE Scale (Borg, ), 11‐point numerical fatigue scale (from 0 to 10) (Micklewright et al . ) and 11‐point numerical Cook scale (from 0 to 10) (Cook et al . ), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked to rate their subjective perception of exertion (RPE), rating of general fatigue and perceived muscle pain using a 6–20 Borg RPE Scale (Borg, ), 11‐point numerical fatigue scale (from 0 to 10) (Micklewright et al . ) and 11‐point numerical Cook scale (from 0 to 10) (Cook et al . ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…RPE, general fatigue, and pain. Participants were asked to rate their subjective perception of exertion (RPE), rating of general fatigue and perceived muscle pain using a 6-20 Borg RPE Scale (Borg, 1982), 11-point numerical fatigue scale (from 0 to 10) (Micklewright et al 2017) and 11-point numerical Cook scale (from 0 to 10) (Cook et al 1997), respectively. The purposeful decision to use a 6-20 RPE scale (rather than a 0-10 scale) was to minimize the possibility that the participants would repeat the same number for both measures.…”
Section: Local Tissue Saturationmentioning
confidence: 99%
“…Further, several of the items included on the scale (eg, Worn Out and Weary) have a more chronic or long‐term connotation, and it may be that participant's ratings on these items were not solely anchored to the acute changes in physiological stress they were experiencing. In support of this, a recent study by Micklewright et al sought to establish the validity of a new fatigue scale, which simply requires participants to rate their level of fatigue on a 0‐10 scale instead of providing ratings for several fatigue‐related adjectives. Although the range of fatigability variables assessed was not as comprehensive as in the current study, the authors reported strong and significant correlations between fatigue ratings and physiological changes related to fatigue .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recent study by Micklewright et al sought to establish the validity of a new fatigue scale, which simply requires participants to rate their level of fatigue on a 0‐10 scale instead of providing ratings for several fatigue‐related adjectives. Although the range of fatigability variables assessed was not as comprehensive as in the current study, the authors reported strong and significant correlations between fatigue ratings and physiological changes related to fatigue . Subsequently, future research is needed addressing the efficacy of individual items on the POMS‐Fatigue scale in capturing state‐levels of fatigue during exercise, possibly leading to the development of separate scales for measuring state‐ and trait‐level fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation